Semantic mapping of participants in legal discourse - Højgaard, Christian Canu (HIPHIL Novum, 2019)
In this paper, I will present a new method of applying open source digital resources for investigating patterns of participants in the legal material of the so-called Holiness Code (Lev 17-26). Although several scholars have tried to explain the internal relationships between the participants in the Holiness Code, the large corpus complicates a systematic and consistent analysis. Developments within computational corpus-linguistics, however, provide new ways of systematic investigations into the discourse of Biblical legal texts. Accordingly, this paper will demonstrate how open source technologies and resources, such as the ETCBC database, text-fabric, R, and Jupyter Notebook, can benefit discourse analysis of the Holiness Code. Using Leviticus 25:23-28 as a case-study, the paper presents a three-step method of creating a semantic map of the participants and their internal relationships. First, semantic role labels are distributed to all participants according to the Role and Reference Grammar theory of the thematic relationship between verb and arguments. Second, all linguistic participant references are tracked and linked to their respective referents. Finally, the formal, linguistic participant tracking and the semantic role labelling are combined to create a semantic map of participants.